Development of Ecotourism Products in Kilim Geopark Based On Tourist Perceptions - Jaafar, Mastura; Nordin, Aleff Omar Shah; Marzuki, Azizan; Abdullah , Shardy (Penerbit UMT, 2015)
Tourism development in Kilim Geopark had a significant impact on the growth of local businesses and has indirectly increased the living standards of the local community. The sustainability of tourism products is crucial to increase the number of tourists in the future and to retain the status of the Geopark. This paper aims to identify the level of tourist satisfaction with the tourism products offered at Kilim Geopark in terms of natural attraction, services, facilities, and product prices. Moreover, this paper discusses the extent of eco-tourism product development in the Kilim Geopark and how to maintain the current level of tourist satisfaction. Based on 341 completed questionnaires, this study reveals that the majority of tourists are interested in new ecotourism products offered at Kilim Geopark. However, significant differences between the levels of satisfaction arise concerning tourism products. Non-Malaysian tourists are perceived to be more satisfied compared to Malaysian tourists based on certain products and selected services. As an emerging tourist attraction, several measures should be considered to improve the competitiveness while maintaining the future development of ecotourism products in Kilim Geopark.